Analisis Kinerja dan Kontribusi Pemungutan Pajak Restoran terhadap Pendapatan Asli Daerah (PAD) di Badan Pendapatan Daerah Kabupaten Bandung - Supryati, Resa; Manjaleni, Rola (JEMSI (Jurnal Ekonomi, Manajemen, dan Akuntansi), 2025)
This study analyzes the performance and contribution of restaurant tax to Regional Original Revenue (PAD) in Bandung Regency. Restaurant tax is one of the primary sources of Regional Original Revenue (PAD), playing a strategic role in supporting regional development. This study adopts a qualitative approach with a descriptive method, gathering data through interviews, observations, and document analysis. The findings indicate that restaurant tax collection in Bandung Regency has achieved a high realization rate, exceeding 100% of the target over the past four years. However, challenges remain, such as limited tax officers, lack of socialization, and the presence of unregistered restaurants as taxpayers. To enhance the effectiveness of restaurant tax collection, strategies such as digitizing tax reporting systems, increasing outreach to business owners, and optimizing supervision by the Regional Revenue Agency (BAPENDA) are necessary. Improving the tax collection system is expected to optimize the contribution of restaurant tax to Regional Original Revenue (PAD) and support sustainable regional economic growth.